Oscilação intra e interanual na reprodução de uma comunidade de aves na Caatinga, um semiárido neotropical - Cavalcanti, Liana Monique Paiva (Universidade Federal Rural do Semi-Árido, 2016)
In semiarid regions, as the Caatinga, the rains distribution can determine the food availability and the intensity of hydric stress. This, with frequency, affects breeding aspects of birds, as time, length and reproduction intensity. In this study we have tested the hypothesis: (1) The breeding of the sampled species is restricted to the rainy season characteristic of the region; (2) Intra-annual variations in the rains’ volume and frequency are correlated with the quantity of individuals and species reproducing; (3) the species of the community reproducing in a way temporally jointly, independent of the feeding guilds. The study was accomplished in Caatinga’s region, with assessments every 14 days of brood patch occurrence. Three reproductive cycles was studied between september-2012 and october-2015. It was utilized the Cross-Correlation Function – CCF to verify the relation existing between the rains and the breeding birds. Altogether, 46 species (377 records) were observed with patches. The reproduction occurred in a seasonal way between february and july, with 94% of the records of patches restricted to the period. The intensity and duration of the breeding (total of individuals and species) was significantly correlated with the rains, when considered the time lag of 14 days. The length (140, 168, and 154 days) and time (march/02 to july/20, February/01 to july/19, February/12 to july/18) of breeding differed between three reproductive cycles. The analysis by feeding guild (insectivore-restrictive, insectivore-frugivorous, insectivore-granivorous and omnivorous) resulted in a similar pattern to general, mainly when it’s considered the correlation and time lag with the rains. Our study indicates that the breeding birds in the Caatinga’s area studied it was not just, generally, related to rainy seasons, as it was break out via answer of short deadline to the rainfall intensity. Including having it period, length and intensity regulated by this climatic factor or by other factors correlated to rains (g.e. food availability)
Keywords: Guilda alimentar; Período reprodutivo; Placas de incubação; Precipitação; Feeding guilds; Reproductive period; Brood patch; Rainfall; CIENCIAS BIOLOGICAS::ECOLOGIA